The association between family health and frailty in preoperative patients with gastric cancers: the mediating role of health literacy and physical activity - Xin, Hanjia; He, Chaozhu; Gu, Yingying; Ma, Xiuxiu; Xiang, Ziying; Gong, Jingjing (Frontiers in Public Health, 2025)
IntroductionFrailty is prevalent among preoperative gastric cancer (GC) patients and significantly affects surgical risk and long-term recovery. Family health may hold substantial potential for mitigating frailty, although the mechanisms underlying this effect remain unclear. This study aims to investigate the impact of family health on frailty in preoperative GC patients, and the mediating effects of health literacy and physical activity.MethodsA total of 240 patients scheduled for radical gastrectomy at a tertiary hospital in China were surveyed using Family Health Scale (FHS), Health Literacy Scale (HLS-SF), International Physical Activity Questionnaire (IPAQ-7), and Tilburg Frailty Indicator (TFI). Data were analyzed using independent t-tests, χ2 tests, Pearson’s correlation, and binary logistic regression. Mediation analysis with Structural Equation Modeling (SEM) was then applied to explore the relationships between variables.ResultsFamily health in preoperative GC patients was negatively correlated with frailty (r = −0.791, p < 0.01) and positively correlated with both health literacy (r = 0.806, p < 0.01) and physical activity (r = 0.464, p < 0.01). Mediating effect analysis indicated that the direct effect of family health on frailty was −0.837, while health literacy and physical activity served as partial mediators in this relationship, with indirect effects of −0.332 and −0.095 (both p < 0.01), respectively. The mediating effects accounted for 33.83% of the total effect.ConclusionFamily health directly affects frailty and also exerts an indirect impact through the mediators of health literacy and physical activity. These findings suggest that healthcare professionals should focus on vulnerable populations with low family health and implement family-centered preoperative frailty interventions. Guiding GC patients to improve health literacy and engage in personalized family-based exercises can help delay or reverse preoperative frailty, promoting long-term recovery outcomes.